Clean and efficient utilization of coal combined with corn straw by synergistic biodegradation. (December 2020) - Guo, Hongyu; Zhao, Shufeng; Dong, Zhiwei; Wang, Qian; Xia, Daping; Jia, Jianbo; Yin, Xiangju; Yu, Hongfei
Abstract: To establish a process for cleaning and efficiently utilizing solid residues and residual liquid after co-fermentation of coal and corn straw, three coal samples combined with corn straw were used. Combustion tests were carried out using the solid residue to compare the changes in calorific value, slagging characteristics and air pollutant emission before and after fermentation. Biogas production experiments were performed using acclimated residual liquid to establish the biomethane production characteristics. Results show that the total calorific value of solid residue after co-fermentation of bituminous coal D, bituminous coal C and corn straw increased by 8.16% and 8.08%, respectively, compared to original samples. The slagging index also decreased during the combustion of solid residues. The diversity of bacterial community structure was the main causes for the significant reduction in air pollutant emissions from the combustion of solid residues. Acclimation experiments improved the removal rate of hemicelluloses from corn straw and increased biomethane production by 45.86%, 10.66% and 60.47%, respectively. This work can improve the clean conversion efficiency of coal and straw, not only reducing environmental pollution, but also transforming waste into clean energy, which has a positive impact on the environment and allows the sustainable use of resources. Highlights: Co-fermentation of coal and corn straw achieved higher methane production. Calorific value of solid residues increased. Atmospheric pollutant emissions and slagging index of solid residues decreased. Methane production increased by acclimation of the residual liquid.